Exploring the Relationship Between Social Media Usage and Mental Health Among Adolescents - Rina Aulia; Arif Setiawan (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This study investigates the effects of social media usage on the mental health of adolescents, focusing on issues such as anxiety, self-esteem, and depression. Using surveys and interviews, the research examines how prolonged exposure to social media content, peer comparison, and cyberbullying contribute to mental health challenges. Findings indicate that while social media fosters connectivity, it can also exacerbate mental health issues, highlighting the need for greater awareness and parental guidance.